Cessie in The Guarantee of Rights of Responsibility Reviewed from The Civil Code - Doni Christian Nainggolan; Daffa Muhammad Nazar; Asmak Ul Hosnah; Yenny Febrianty (Jurnal sosial dan sains, 2023)
Background: Home Ownership Credit (KPR) activities are generally held by the Bank. However, often in mortgage practices there are often conflicts, one of which is bad debt. One solution that is often used by banks as creditors is to transfer receivables (cessie) to the mortgage object. But on the other hand, using the implementation of the cessie causes new problems, namely customers as debtors often object to the decision of the cessie. Purpose: The purpose of the study is to find out and analyze the legal certainty of the cessie without the consent and knowledge of the debtor connected with the Civil Code and to know and review the description of the procedure of the cessie creditor against third parties as new creditors based on the Civil Code. Methods: The method used is normative juridical, using analytical descriptive specifications, through literature studies and field studies, as well as data collection techniques, followed by data analysis. Results: The research results show that online learning is not fully effective due to various inhibiting factors, and students' learning motivation is still not optimal. Conclusion: Certainty of Cessie rules without the consent and knowledge of the debtor Connected using the KUHPer still does not regulate specifically regarding cessies, especially related to the implementation mechanism, so that this causes new conflicts such as the other error, not infrequently there are multiple interpretations in the implementation of cessie, especially in mortgage practice. Legal certainty of cessie still relies on Article 613 of the Civil Code to be the basis for the creditor's cessie. but on the other hand, the existence of multiple interpretations in interpreting Article 613 of the Civil Code causes objections made by debtors as cessus both through litigation and non-litigation.